2013
DOI: 10.1098/rspb.2012.2359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parasites on salmon recruitment in the Northeast Atlantic Ocean

Abstract: Parasites may have large effects on host population dynamics, marine fisheries and conservation, but a clear elucidation of their impact is limited by a lack of ecosystem-scale experimental data. We conducted a meta-analysis of replicated manipulative field experiments concerning the influence of parasitism by crustaceans on the marine survival of Atlantic salmon (Salmo salar L.). The data include 24 trials in which tagged smolts (totalling 283 347 fish; 1996-2008) were released as paired control and parasitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 60 publications
(111 reference statements)
2
110
3
Order By: Relevance
“…This means that, by necessity, manipulative studies are rare compared with correlative studies. Even when manipulative studies have been possible [3,69], debate and controversy have persisted [70,71]. Another major challenge is the fact that a negative statistical result does not necessarily translate to a negative biological conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This means that, by necessity, manipulative studies are rare compared with correlative studies. Even when manipulative studies have been possible [3,69], debate and controversy have persisted [70,71]. Another major challenge is the fact that a negative statistical result does not necessarily translate to a negative biological conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the fish were treated with a parasiticide that provided temporary protection from infection by sea lice in early marine life, while the other half received a control treatment. A meta-analysis of 24 paired-release experiments (totalling 283 347 fish) showed that lack of treatment (a surrogate of parasite exposure) decreased survival of returning adults by 39% [3]. Although there was variation among trials in effectiveness of treatments, with some trials showing no evidence of effect and others showing a strong effect, collective examination revealed clear evidence of a positive effect of the parasiticide treatment on salmon recruitment (figure 5d).…”
Section: Implications For Conservation and Fisheriesmentioning
confidence: 99%
See 3 more Smart Citations